Krondor, the assassins - Feist, Raymond E. (London : HarperCollins, 2000)
Concerned about a rash of unexplained assassinations in his kingdom, Prince Arutha calls on his most trusted agent, Squire James, to discover the source of the deadly epidemic.
Adult.
Adult
Keywords: Assassins -- Fiction; Magic -- Fiction; Midkemia (Imaginary place) -- Fiction; Assassins -- Fiction; Magic -- Fiction; Midkemia (Imaginary place) -- Fiction; Fantastic fiction